Assessing the mental health needs of Yazidi adolescents and young adults in an Iraqi Kurdi IDP Camp: a focus group study - Roberto Benoni; Chiara Giacomelli; Giuditta Vegro; Faroq Hamo; Riccardo Avesani; Pietro Albi; Michela Gatta; Francesca Moretti (International Journal for Equity in Health, 2024)
Abstract Background Internally displaced people (IDP) in Iraq are 1.2 million (as March 2023). Protracted refugee status endangers the mental health, especially of minorities who survived persecution and conflict, such as the Yazidis. This study aims to identify the mental health needs of Yazidi adolescents and young adults (AYA) in the IDP camp of Bajed Kandala (Iraqi Kurdistan). Methods A focus group discussion (FGD) study was conducted between April and August 2022. The FGDs involved AYAs, as well as the staff of the clinic of the Bajed Kandala camp. An inductive approach was adopted referring to the ’theme’ as the unit of content analysis of the text. All FGDs were recorded and transcribed. The analysis was carried out independently by two researchers. The inter-rater agreement was assessed through the Cohen’s k. Results A total of 6 FGDs were conducted. The participants were 34 of whom 21 (61.8%) females with a median age of 18.5 years (IQR 17.0–21.0). A total of 156 themes were found as relevant to the objective of this study. Four main areas and twelve subareas of needs in mental health were identified. The interrater agreement over the main area and subareas was good (κ = 0.78 [0.95CI 0.69–0.88], κ = 0.82 [0.95CI 0.73–0.91], respectively). The four areas had a similar frequency: Activities (28.2%), Individual (27.6%), Social relationships (22.4%) and Places/setting (21.8%). The subareas ‘community’ and ‘internal resources’ were labelled as negative 85.7% and 61.9% of the time, respectively. These sub-areas referred to stigma and self-stigma towards mental health. The subarea ‘female condition’ was always considered as negative, as well as the subareas ‘camp’ and ‘tent’ referring to housing as an important social determinant of mental health. Conclusions Community stigma and self-stigma are two still important factors preventing the achievement of mental well-being. Alongside these, a gender gap in mental health was identified in the FGDs. These factors should be taken into account in order to guide future mental health interventions in refugee camps.